Utilization of Toddler Development Stimulation Videos in Improving Developmental Milestones: - Istiqomah, Nurul; Sari, Anggi Luckita; Yuliastuti, Estin; Asjad, Syahria Ulayya; Rasyid, Wulan Saputri (Universitas Muhammadiyah Surakarta, 2025)
Children under five years old are the golden age for a child to acquire excellent skills such as perception, interaction, speaking, etc., and therefore, developmental screening at this age to identify developmental problems in children early and provide treatment. Families, especially caregivers, provide the care needed by children to develop in the early years, so they need support to provide stimulation. The problem of gross motor development at an early age is the greatest and the older the age, the more advanced developmental problems such as fine motor skills, walking. The purpose of this study was to determine the effect of educational video stimulation of toddler development on increasing developmental milestones. This research method uses a quasi-experimental design, one group pre-test post-test. This research was conducted at the Posyandu Balita Sahabat Masyarakat, Kusumadilagan, RT 04 / RW 12, Joyosuran, Pasarkliwon, Surakarta. The sample in this study was 20 pairs of mothers and children with purposive sampling techniques. The research instrument was in the form of a pre-screening development questionnaire (KPSP). The results of the study obtained a significance value of 0.002 from the pre-test and post-test values, so it can be concluded that there is an effect of providing educational videos on toddler development stimulation on increasing development milestones.